Barriers to Research Perceived by Medical Students of Private Medical College, Lahore- Pakistan - Aaiza Azhar, Momina Qaisar, Mahnoor Hamid, Moneeba Amna, Fatima Tanveer, Muhammad Ashraf Chaudhry, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To identify the major barriers to conducting research perceived by medical students and their association with various years of study and gender. Methodology: This was an analytical cross-sectional study conducted from 9th March 2021 to 6th June 2021. It was conducted among the medical students of all years studying in Combined Military Hospital Lahore Medical College (CMHLMC) & Institute of Dentistry (IOD). Non- probability convenient sampling technique was used. The questionnaire was self-administered and data was analyzed by using SPSS version 20.0.Descriptive statistics of qualitative variables were calculated as frequencies and percentage. Chi-square test of significance was used to see impact of gender and year of study on barriers perceived. P value<0.05 was considered statistically significant. Results: There was significant difference in barriers perceived by male and female students (p <0.05). The most prevalent barrier in males was extracurricular activities (p=0.001) while major barrier in females was fatigue (p=0.006). Prevalence of barriers was found to be greater among students of 2nd year MBBS (39.3%) and 4th year MBBS (31.3%).The most significant barrier among 2ndyear MBBS was fatigue (p=0.006) while in 4th year MBBS the common barriers perceived were lack of previous exposure (p=0.003), uncooperative colleagues (p=0.003) and finding a mentor (p=0.018). Practical implications: By using this research as a template we can identify ways in which our education system can probe about flaws in promotion and execution of research among students and how to rectify these so that more students can be urged to go forth in medical field as competent researchers so to advance current methods of treatment and bring forth new queries .Pakistan being a third world country is in dire need of young medical professionals who can bring about a new perspective in field of medicine and we can only do so by facilitating them . This article will give an insight in the current difficulties faced by students whether from personal or administrative point of view which is proving to hinder their progress. Conclusion: The results of study showed that major barriers perceived by medical students were curriculum overload, finding a mentor, lack of previous exposure to research. There was significant difference in barriers perceived by various classes and males and females. Keywords: Barriers, medical students, research, gender, medical research, Pakistan, curriculum